ELSIcon2024: Reimagining the Benefits of Genomic Sciences. - Dolan, Deanne Dunbar; Cho, Mildred K.; Lee, Sandra Soo-Jin (American Journal of Bioethics, 2025)
The article discusses the 6th ELSI Congress, ELSIcon2024, which focused on the ethical, legal, and social implications (ELSI) of genomic sciences, held from June 10–12, 2024, in New York City. The congress brought together over 300 participants from 19 countries to explore innovative research and scholarship on the benefits of genomics, featuring a variety of presentations and discussions. Contributions from various authors highlighted the need for structural changes in academia and healthcare to ensure equitable access to genomic medicine, emphasizing the importance of addressing social norms and institutional constraints that affect reproductive autonomy and access to services for children with genetic conditions. The discussions underscored the necessity of rethinking governance structures and centering equity in the deployment of genomic science.